Regulated Expression of Focal Adhesion Kinase-Related Nonkinase, the Autonomously Expressed C-Terminal Domain of Focal Adhesion Kinase - Nolan, Kate (American Society for Microbiology, 1999)
Focal adhesion kinase (FAK) has been implicated in cellular processes that control cell adhesion, migration, cell cycle progression, and apoptosis. FRNK (FAK-related nonkinase) is the autonomously expressed, noncatalytic C-terminal portion of FAK. When ectopically expressed in cells, FRNK has been shown to act as a negative regulator of FAK activity, inhibiting cell spreading, migration, and cell cycle progression. The mechanisms that regulate FRNK expression during embryonic development and the functional role of FRNK in normal cell homeostasis remain poorly understood. Herein we show that FRNK expression in chicken cells is directed by an alternative promoter residing within an intron of FAK, positioned 3′ of the exon encoding sequences for the catalytic domain and 5′ of the exon encoding sequences for the C-terminal domain of FAK (e.g., FRNK). Using probes specific for FRNK, we show that FRNK expression occurs early in chicken embryogenesis, being readily detected at day 3, 6, or 9. Late in embryogenesis, at day 18, FRNK is expressed in a tissue-specific manner, predominately in lung and intestine cells. Western blot analysis of mouse tissues with a FAK-specific antibody revealed the expression of FRNK in the mouse lung. Reverse transcriptase PCR analysis of mouse lung RNA revealed the presence of spliced FRNK mRNAs containing 5′ untranslated sequences derived from a positionally conserved exon present in the mouse genome. FAK is the first example of a tyrosine kinase regulated by a domain under the control of an alternative intronic promoter. It is also the first example of a focal adhesion-associated protein regulated by such a mechanism and thus represents a novel means for the modulation of cell adhesion signaling.